FOREIGN EXPERIENCE OF COMMERCIALIZATION OF INNOVATIONS AND ACTIVATION OF INTEGRATION PROCESSES IN THE INNOVATION SPHERE - Baula, O.V. (The actual problems of regional economy development, 2021)
The purpose of the article is to monitor foreign experience in the commercialization of innovations and intensification of integration processes in the innovation sphere. Methods of formalization, analogies, analysis, comparison were used in the research process to fulfill the outlined goal. The information base of the study is the materials of the European Commission, materials of monographs, scientific articles of domestic and foreign scientists, analytical reviews. The systematization of works of domestic and foreign scientists is carried out in order to provide a comprehensive interpretation of innovation in modern business conditions. The rating of the world countries according to the Global Innovation Index in 2015-2021 (TOP-20 and Ukraine) is analyzed. The range of practical means and tools for ensuring innovative development and increasing the level of commercialization of innovations used by the countries of the World Economic Area has been studied. Assessing the best practices experience of intensifying innovation, it was concluded that the priority task of innovation countries is to build an innovation chain from the generation of an idea to its implementation in the business environment. The article summarizes the foreign integration experience of financial, organizational and regulatory support for the commercialization of innovations, as well as outlines measures in this area that can be adapted for implementation in domestic innovation practice. The scientific novelty of the obtained results is the substantiation of the direct impact of commercialization of innovations on the country's competitiveness, the interpretation of the definition of "innovation" is clarified by emphasizing the need for their consistency and continuity of production, as well as the optimality of innovation and management infrastructure at micro, macro and meso levels. Measures to increase the level of commercialization of innovations for integrated structures (science, state, business) have been singled out from the best foreign experience of the countries - innovation leaders, which will help increase the efficiency of the whole chain of creating an innovative product in domestic practice. The results of the study can be used in the formation of innovation policy measures for the formation of strategic directions to increase the level of commercialization of innovations.